HUBUNGAN ANTARA UMUR, UMUR MULAI SAKIT, LAMA SAKIT DENGAN LED, CRP, DAS28-LED DI ARTRITIS REUMATOID - J. Soeroso; FM. Judajana (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease affecting joints with a high disability and prematuredeaths. The successful treatment depends on the monitoring and control of the disease activities. Age, Age at onset and its duration arerelated to the dynamics of the related activities in RA. The objective of the study is to determine the associations between the age, theAge at onset and its duration with the related activity markers like ESR, CRP and DAS28-ESR in RA. A cross sectional study was doneon 44 patients suffering from RA obtained from the Rheumatology Outpatient Clinic at the Dr Soetomo Provincial Hospital, Surabaya.They were diagnosed using the American College of Rheumatology (ACR) Criteria 1987. Kruskal-Wallis tests were used to determine theassociations between age (years), age at onset (years), its duration (months) with ESR (mm/hour), CRP (n) and DAS28-ESR respectively.Analysis results of the Kruskal-Wallis test includes: The age for the high ESR, namely: age ≥20 vs. age <20, p=0.035; age ≥30 vs.age<30, p=0.002; age ≥40 vs. age<40, p=0.000; and age ≥50 vs. age<50, p=0.047. The age for the high DAS28-ESR score namely:age≥30 vs. age<30, p=0.020; and age ≥40 vs age<40, p=0.013. The disease duration for the high ESR namely: disease duration ≥96vs. Disease duration <96, p=0.044. The disease duration for the high CRP namely: disease duration ≥84 vs. disease duration <84,p=0.015 and disease duration ≥96 vs. disease duration <96, p=0.029. All ages at onset segments were not associated with the high ESR,CRP as well as with the high DAS28-ESR. In this study it can be concluded that the age of patients suffering from RA is associated withhigh ESR. The older the age of the patients the higher will be the ESR. Older age is also associated with the high DAS28-ESR. The longerthe disease duration will be related with the high ESR, as well as the high CRP. ESR may be considered as a practical tool for measuringthe disease activity in RA, mainly for outpatients.